Peningkatan Keterampilan Guru Biologi SMA Kota Palangka Raya melalui Pelatihan Pembuatan Preparat Histologi Jaringan: Improving the Skills of High School Biology Teachers in Palangka Raya City through Training in Making Tissue Histology Preparations - Tuju, Fandi; Gunawan, Yohanes Edy; Wulandari, Meyta (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Tissue histology preparations are the gold standard for determining the pathological state and changes in cells or tissues. Basic tissue histology preparation knowledge is essential for correctly applying tissue processing steps in the histology laboratory. Teachers' skills in making histology preparations need to be improved. The participants in this activity were 12 high school biology teachers in Palangka Raya City who were members of the MGMP Biology Teacher. This activity aims to improve the skills of high school Biology teachers through training in making tissue histology preparations, and it is hoped that this training can provide solutions to Biology practicum in schools, which are certainly packaged to be more interesting, with the advantage that these preparations can be stored and used for an extended period. This activity was carried out at the 2nd Floor Laboratory of the PPIIG Building, Universitas Palangka Raya, in November 2023. The implementation method is training biology teachers to prepare tissue histology. The training began with the delivery of material, followed by discussion, pre-test, training, post-test, and participant testimonials. The results of the post-test assessment showed a significant increase after this training, so it can be concluded that there was an increase in participants' knowledge in making tissue histology preparations.